2022
DOI: 10.1093/nsr/nwac246
|View full text |Cite
|
Sign up to set email alerts
|

Underwater acoustic metamaterials

Abstract: Acoustic metamaterials have been widely investigated over the past few decades and have realized acoustic parameters that are not achievable using conventional materials. After demonstrating that locally resonant acoustic metamaterials are capable of acting as subwavelength unit cells, researchers have evaluated the possibility of breaking the classical limitations of the material mass density and bulk modulus. Combined with theoretical analysis, additive manufacturing, and engineering applications, acoustic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 173 publications
0
9
0
Order By: Relevance
“…17 Dong et al reported a kind of bioinspired metagel with gradient acoustic impedance, which was capable of establishing broadband acoustic transmission between two mismatching media. 18 However, the above work focused on the transmission properties at relatively low frequencies (<0.3 MHz), which is unsuitable for transcranial ultrasound that typically employs a higher frequency of 0.6−3 MHz. 19,20 In this study, we propose a novel approach to overcome the limitations of existing acoustic metamaterials and matching layers for transcranial ultrasound, which often suffer from rigid structures or low operational frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Dong et al reported a kind of bioinspired metagel with gradient acoustic impedance, which was capable of establishing broadband acoustic transmission between two mismatching media. 18 However, the above work focused on the transmission properties at relatively low frequencies (<0.3 MHz), which is unsuitable for transcranial ultrasound that typically employs a higher frequency of 0.6−3 MHz. 19,20 In this study, we propose a novel approach to overcome the limitations of existing acoustic metamaterials and matching layers for transcranial ultrasound, which often suffer from rigid structures or low operational frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve suitable impedance matching over a wide frequency band, Pedersen et al conducted theoretical research and found that a matching layer with an exponential impedance exhibited the most stable high sound energy transmission efficiency over a wide frequency range . Dong et al reported a kind of bioinspired metagel with gradient acoustic impedance, which was capable of establishing broadband acoustic transmission between two mismatching media . However, the above work focused on the transmission properties at relatively low frequencies (<0.3 MHz), which is unsuitable for transcranial ultrasound that typically employs a higher frequency of 0.6–3 MHz. , …”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Nevertheless, given the complexity and variability of the surrounding environment, single‐function stealth technologies such as visible light stealth, infrared stealth, radar stealth, etc., face challenges in adequately addressing modern detection system requirements. [ 3–6 ] Therefore, there is an urgent need to develop advanced multispectral‐compatible stealth materials and technologies.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Nevertheless, given the complexity and variability of the surrounding environment, single-function stealth technologies such as visible light stealth, infrared stealth, radar stealth, etc., face challenges in adequately addressing modern detection system requirements. [3][4][5][6] Therefore, there is an urgent need to develop advanced multispectral-compatible stealth materials and technologies. The term multifunctional stealth technology commonly encompasses radar-infrared compatible stealth, infrared and laser compatible stealth, visible light-near infrared-far infrared, and other multi-band stealth.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] As the counterpart of electromagnetic metasurfaces, [3][4][5] acoustic metasurfaces have provided a novel approach for designing flat and compact devices that can manipulate sound waves in a two-dimensional (2D) planar situation. [6][7][8] In particular, acoustic gradient metasurfaces (AGMs) usually consist of periodic arrays of structurally graded subwavelength blocks that are designed as Helmholtz resonators [9,10] or coiled-up space structures. [11,12] AGMs introduce an in-plane phase gradient, which is equivalent to an additional wave vector, thus altering the fundamental law of reflection and refraction of acoustic waves at the interface.…”
mentioning
confidence: 99%